Growth hormone secretion decreases with age in paediatric Prader‐Willi syndrome. (12th January 2015) - Cohen, M.; Harrington, J.; Narang, I.; Hamilton, J.
Summary Objective Growth hormone deficiency is a common feature of Prader‐Willi syndrome; however, biochemical deficiency is not uniformly demonstrated. Criteria for GH treatment in paediatric PWS vary with some countries requiring documentation of biochemical GH deficiency. Data regarding the significance of age in the interpretation of GH stimulation test results, particularly in infants, are lacking. We aimed to assess age‐related trends in the prevalence of biochemical GH deficiency in infants and children with PWS. Design A retrospective chart review was conducted. Data from children with Prader‐Willi syndrome that had GH stimulation tests performed at the Hospital for Sick Children in Toronto between the years 2000 and 2012 were collected. Patient Charts of 47 children 0·4–15·5 years of age with PWS that had GH stimulation tests were reviewed. Measurements Biochemical GH status in relation to age and body mass index. Results Thirty‐two of 47 patients (68%) were biochemically GH deficient. GH deficiency was significantly associated with older age (r = 0·45, P = 0·02) and higher body‐mass‐index z‐score (r = 0·45, P = 0·02). Biochemical GH deficiency was less prevalent up to 18 months of age (3/11 27%) compared with older children (29/36 [81%]; P = 0·001). A higher prevalence of GH deficiency was also detected in obese patients (14/16 [88%]) compared with nonobese patients (18/31 [58%]; P = 0·04). Conclusions The utility of performing GH stimulation tests as an indication of GH status under 18 months of age in Prader‐Willi syndrome is questionable. If performed, results should be carefully interpreted in the context of age.